Development of E-LKPD Based on Technology Pedagogical and Content Knowledge (TPACK) in High School Mathematics Subjects - Syafrudin; Rayendra; Zelhendri Zen; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2025)
Mathematics learning in Class X SMAN 1 Pelangiran remains suboptimal due to the dominance of lecture-based methods and conventional teaching materials, resulting in passive student engagement and low learning outcomes (only 41.38% completeness). This study aimed to develop a TPACK-based Electronic Student Worksheet (E-LKPD) for geometry materials to enhance learning effectiveness. TPACK integrates technological, pedagogical, and content knowledge, while E-LKPD promotes interactive, technology-assisted learning. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the E-LKPD was designed with multimedia elements such as videos, quizzes, and digital navigation. Expert validation results indicated high feasibility: material (95.4%), media (80%), and language (90.55%). Practicality tests showed the E-LKPD was very practical for teachers (90.95%) and students (85.25%). Effectiveness was demonstrated through an increase in students’ average scores from 17.31 in pre-test to 61.21 in post-test, with and N-Gain of 57%. The findings conclude that the TPACK-based E-LKPD is valid, practical, and effective in supporting more interactive and adaptive mathematics learning.